A indenização punitiva como possibilidade de garantia efetiva ao direito constitucional de defesa do consumidor - Petry, Alexandre Torres (2014)
The following study is focused on the research line of the constitutional foundations of public law and private law, having its specific field in the interaction between consumer law and tort law. The outline of the proposed research is based on a very controversial topic, as it addresses a new type of damage, which is not excessively provided for in the legislation, the result of doctrinal and jurisprudential construction: the societal damage. This damage, which means a simplification damage resulting from an intentional or negligent serious act, rather than injuring the author of a reparatory lawsuit, harms the whole society, or particular group, due to the lowering of its level by a highly reprehensible act, therefore becoming the theoretical foundation of punitive damages. These indemnities do not match the existing punitive damages in common law legal systems, as they have significant differences, although it is undeniable that its inspiration is evident in this institute of comparative law. Punitive damages are also not synonymous with moral damages, whether in the individual or collective sphere. Therefore the punitive damages incorporate the fundamentals and the proper outlines, this then becomes the object of the work: to fully exploit the feasibility of adopting in the current Brazilian legal context punitive damages, trying to delineate the limits, functions and their relevance. At first, the analysis of consumer law shall be confronted, assessing its current level of efficiency and effectiveness, addressing the existing problems and the traditional answers given. In the era of mass-market relations and, therefore, "massive damage", it will be noted that the solutions found so far are not sufficient enough to reduce conflicts and systematic disrespect to consumers, often made purposely by major suppliers that frequently perform an economic analysis of the "cost-benefit", concluding that on certain occasions harming consumers may be profitable. Once this situation is analyzed, the necessary upgrading of liability will be held, which must surpass the classic paradigm of recovery, to also seek, through punishment, the needed deterrence, and as a secondary plan, the desired prevention. In this context, punitive damages, which aim to protect the societal damage, will be identified as an important and necessary tool for the effective guarantee of the constitutional right of the consumer, assuming an important role in a new era in which, rather than repairing the consumers damages, they will be avoided, therefore society becomes more caring, fraternal and peaceful, with its core in human dignity.